Ionic Origin of Electro-osmotic Flow Hysteresis - Lim, Chun Yee (2016)
Electro-osmotic flow, the driving of fluid at nano- or micro- scales with electric field, has found numerous applications, ranging from pumping to chemical and biomedical analyses in micro-devices. Electro-osmotic flow exhibits a puzzling hysteretic behavior when two fluids with different concentrations displace one another. The flow rate is faster when a higher concentration solution displaces a lower concentration one as compared to the flow in the reverse direction. Although electro-osmotic flow is a surface phenomenon, rather counter intuitively we demonstrate that electro-osmotic flow hysteresis originates from the accumulation or depletion of pH-governing minority ions in the bulk of the fluid, due to the imbalance of electric-field-induced ion flux. The pH and flow velocity are changed, depending on the flow direction. The understanding of electro-osmotic flow hysteresis is critical for accurate fluid flow control in microfluidic devices, and maintaining of constant pH in chemical and biological systems under an electric field.